Effect of pre-twist in the spinning triangle on yarn strength. Issue 3 (8th February 2022) - Shao, Ruiqi; Cheng, Longdi; Xu, Zhiwei; He, Shanshan
Abstract: The spinning triangle is the morphologic transformed area of fiber assembly, which influences the yarn structure and appearance quality. In the spinning triangle, the pre-twist was formed due to the twisting torque, it changed part of fibers delivered path and thus the way of fibers arrangement in yarn body. In this paper, a model of spinning triangle with pre-twist was proposed to study the effects of pre-twist position and other spinning parameters on the fiber tension in the spinning triangle and yarn strength. Three representative cases were discussed respectively, namely the pre-twist region on the left side, middle position, and right side. The following results were obtained: (1) yarn strength shown a W-shape tendency with the pre-twist region moved from left to right; (2) the increase of inclination angle boosted yarn strength and the increase of height of spinning triangle made the decrease of yarn strength when fiber buckling was considered; (3) the increase of spinning tension promoted yarn strength, but did not change the influence of pre-twist on yarn strength.